For the good of humanity : Ludwik Rajchman, medical statesman - Balinska, Marta Aleksandra (Central European University Press, 1998)
In this biography of Ludwik Rajchman, Marta A. Balinska paints a portrait of a true hero of our times. He was born in Poland in 1881 and was an exponent of humanitarian intervention and defender of colonized people, as adept in secret diplomacy as in organizing vast anti-epidemic campaigns. He inspired the creation of WHO and the foundation of UNICEF, of which he became the first chairman. Progressive but opposed to all dogmas, he was forced by McCarthyism to flee the U.S. and soon became an object of suspicion in the Soviet bloc, finding himself estranged from his beloved Poland. As the story of this remarkable life unfolds, the reader is given a behind-the-scenes glimpse of the major events that shaped the twentieth century. Using family archives and documentary sources from a dozen countries, the author brilliantly reconstructs the career of a man who was not only the first médecin sans frontiere but also an intellectual with an exceptional sense of the universal.